2018
DOI: 10.1073/pnas.1806202115
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of coactivator engagement mechanism enables small-molecule allosteric modulators

Abstract: SignificanceTranscriptional coactivators and their partner transcription factors have been labeled as intrinsically disordered, fuzzy, and undruggable. We propose that the identification of conserved mechanisms of engagement between coactivators and their cognate activators should provide general principles for small-molecule modulator discovery. Here, we show that the structurally divergent coactivator Med25 forms short-lived and dynamic complexes with three different transcriptional activators and that confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(76 citation statements)
references
References 37 publications
3
72
1
Order By: Relevance
“…ETV/PEA3•Med25 interactions represent an ideal system to study dynamic TAD•ABD interactions for several reasons. First, previous studies indicated that interaction of ETV/PEA3 family member ETV5 with the Med25 ABD is typical of a dynamic TAD•ABD complex (30,32); the binding surface is shallow, both acidic and hydrophobic amino acids of the TAD determine affinity and activity, and multiple bound conformational states were detected by both NMR and kinetic analyses. Second, our previous studies of the ETV5•Med25 complex showed that the bound conformational ensemble is directly accessible by transient kinetic analysis.…”
Section: Etv/pea3•med25 Ppis As a Model System For Dynamic Tad•abd Inmentioning
confidence: 99%
See 4 more Smart Citations
“…ETV/PEA3•Med25 interactions represent an ideal system to study dynamic TAD•ABD interactions for several reasons. First, previous studies indicated that interaction of ETV/PEA3 family member ETV5 with the Med25 ABD is typical of a dynamic TAD•ABD complex (30,32); the binding surface is shallow, both acidic and hydrophobic amino acids of the TAD determine affinity and activity, and multiple bound conformational states were detected by both NMR and kinetic analyses. Second, our previous studies of the ETV5•Med25 complex showed that the bound conformational ensemble is directly accessible by transient kinetic analysis.…”
Section: Etv/pea3•med25 Ppis As a Model System For Dynamic Tad•abd Inmentioning
confidence: 99%
“…Second, our previous studies of the ETV5•Med25 complex showed that the bound conformational ensemble is directly accessible by transient kinetic analysis. (32) The models of TAD•ABD molecular recognition can thus be dissected in this system without the loss of critical conformational information to equilibrium averaging. Third, the ETV/PEA3 family of transcription factors serves as an excellent natural system to test the relationship between TAD sequence and recognition; they contain almost identical arrangements of acidic and hydrophobic residues across the TAD sequence, especially within the helical binding region that undergoes coupled folding and binding with Med25,(30) but the identity of specific residues varies slightly ( Fig.…”
Section: Etv/pea3•med25 Ppis As a Model System For Dynamic Tad•abd Inmentioning
confidence: 99%
See 3 more Smart Citations